Langerhans Cell Histiocytosis in Bilateral Mastoid Cavity - Kazım Bozdemir; Behçet Tarlak; Hasan Çakar; Ahmet Doblan; Ahmet Kutluhan; İmdat Dilek; Nuran Adıyaman Süngü (Case Reports in Otolaryngology)
A 39-year-old male was admitted to our clinic with symptoms of headache, dizziness, nausea, otalgia, otorrhea, tinnitus, and hearing loss in both ears for 3 weeks. Physical examination revealed edema in the tympanic membrane and external ear canal, and pain by palpation in the mastoid area bilaterally. There was no nystagmus, and the rest of the physical examination was otherwise normal. Temporal bone high resolution computed tomography (CT) showed a lesion causing erosion in the mastoid cortex, tegmen tympani, ossicles, and in the bone covering the sigmoid sinus bilaterally. There was also erosion in the superior semicircular canal and petrous bone on the left side. Cortical mastoidectomy was performed under general anesthesia. Histopathologic examination of the tissue revealed Langerhans cell histiocytosis (LCH). In this paper a case with LCH, presenting with bilateral mastoid involvement which has been rarely reported in the literature, is discussed with the existing literature.